Experimental and Metabolic Modeling Evidence for a Folate-Cleaving Side-Activity of Ketopantoate Hydroxymethyltransferase (PanB) - Thiaville, Jennifer J.; Frelin, Océane; García-Salinas, Carolina; Harrison, Katherine; Hasnain, Ghulam; Horenstein, Nicole A.; Díaz de la Garza, Rocio I.; Henry, Christopher S.; Hanson, Andrew D.; de Crécy-Lagard, Valérie (Frontiers in Microbiology, 2016)
Tetrahydrofolate (THF) and its one-carbon derivatives, collectively termed folates, are essential cofact¬ors, but are inherently unstable. While it is clear that chemical oxidation can cleave folates or damage their pterin precursors, very little is known about enzymatic damage to these molec-ules or about whether the folate biosynthesis pathway responds adaptively to damage to its end-pro¬¬ducts. The presence of a duplication of the gene encoding the folate biosynthesis enzyme 6-hydr¬oxymethyl-7,8-dihydropterin pyrophosphokinase (FolK) in many sequenced bacterial gen-omes combined with a strong chromosomal clustering of the folK gene with panB, encoding the 5,10-methylene-THF-dependent enzyme ketopantoate hydroxymethyltransferase, led us to infer that PanB has a side activity that cleaves 5,10-methylene-THF, yielding a pterin product that is recycled by FolK. Genetic and metabolic analyses of Escherichia coli strains showed that over-expression of PanB leads to accumulation of the likely folate cleavage product 6-hydroxy¬methyl-pterin and other pterins in cells and medium, and – unexpectedly – to a 46% increase in total fol-ate content. In silico modeling of the folate bio¬syn¬thesis pathway showed that these observations are consistent with the in vivo cleavage of 5,10-methylene-THF by a side-activity of PanB, with FolK-mediated recycling of the pterin cleavage product, and with regulation of folate biosynth-esis by folates or their damage products.